1975
DOI: 10.1073/pnas.72.2.664
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid chain flexibility in the membranes of normal and transformed fibroblasts.

Abstract: Fatty acid spin labels were used to measure the inherent flexibility of the lipid acyl chains in intact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
0

Year Published

1976
1976
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 30 publications
5
42
0
Order By: Relevance
“…Von Dreele and Williams (19) recently reported the absence of change in membrane fluidity during the development of D. discoideum, using 16-nitroxide stearic acid spin labels which detected the isotropic motion of the lipids at a given temperature. The lack of any difference in membrane fluidity is also in accord with results from normal and transformed mouse 3T3 cells (5).…”
Section: Discussionsupporting
confidence: 73%
“…Von Dreele and Williams (19) recently reported the absence of change in membrane fluidity during the development of D. discoideum, using 16-nitroxide stearic acid spin labels which detected the isotropic motion of the lipids at a given temperature. The lack of any difference in membrane fluidity is also in accord with results from normal and transformed mouse 3T3 cells (5).…”
Section: Discussionsupporting
confidence: 73%
“…PC (5,10) in the Light and Dark. Attempts to incorporate PC(5, 10) into oat leaf protoplasts were successful (Fig.…”
mentioning
confidence: 99%
“…Me-I5,10), 2-(l -carboxydecyl)-2-hexyl-4,4-dimethyl-3-oxazolidinyloxyl methyl ester; maleimide probe, 4-maleimido-2,2,6,6-tetramethylpiperidinooxyl; iodoacetamide probe, 4-(2-iodoacetamide)-2,2,6,6-tetramethylpiperidinooxyl; TEMPO, 2,2,6,6-tetramethylpiperidinooxyl; TEMPAMINE, 2,2,6,6-tetramethyl-4-aminopiperidinooxyl; cholestane probe, 4',4'-dimethylspiro [5a-cholestane-3,2'-oxazolidinJ-3'-yloxyl; androstane probe, 17,8-hydroxy -4',4' -dimethylspiro[5a-androstane-3,2' -oxazolidin]-3' -yloxyl; 2N8, 2-methyl-2-hexyl-4,4-dimethyl-3-oxazolidinyloxyl; 5N10, 2-n-butyl-2-n-pentyl-4,4-dimethyl-3-oxazolidinyloxyl; PC (5,10) Figure 5 and settings for I (1,14), Me-1(5,10), 5N10, and the androstane and cholestane probes were as in Figure 1. The sample temperature was controlled by a Varian variable temperature controller and was monitored by an Omega model 250 thermocouple positioned within the cuvette.…”
mentioning
confidence: 99%
“…This alteration in the average number of fatty acid double bonds in the lipids derived from erythrocytes of normal and CHS mice or humans can account for the observed differences in membrane fluidity . Gaffney (19) has shown that a 10% increase in the number of unsaturated fatty acid chains can result in a significant change in membrane fluidity. Her studies were carried out in a model bilayer system of synthetic dioleoyl and diarachidonoyl lecithins.…”
Section: Discussionmentioning
confidence: 99%